Combined aortic and mitral valvular surgery with the Intuity rapid deployment prosthesis in the aortic position: Operative tips and tricks. Issue 4 (8th February 2022) - Singh, Navneet; Nand, Parma
Abstract: The Edwards Intuity valve is a rapid deployment prosthesis designed for the aortic position. There is a paucity of literature on the use of the Intuity valve in combined aortic and mitral double valvular surgery. We present a case that highlights our novel surgical technique for implanting the Intuity valve in the aortic position following insertion of a conventional sutured bioprosthetic valve in the mitral position.